2002
DOI: 10.1096/fj.02-0338fje
|View full text |Cite
|
Sign up to set email alerts
|

The endocannabinoid system and the molecular basis of paralytic ileus in mice

Abstract: The endocannabinoid system (i.e., the cannabinoid receptors and their endogenous ligands) plays an important role in the physiological control of intestinal motility. However, its participation in intestinal pathological states is still poorly understood. In the present study, we investigated the possible role of the endocannabinoid system in the pathogenesis of paralytic ileus, a pathological state consisting of decreased intestinal motility following peritonitis, surgery, or other noxious situations. Ileus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 47 publications
(95 reference statements)
6
72
0
2
Order By: Relevance
“…Interestingly, VIP receptor desensitization did not affect the I sc response to capsaicin. Similarly, experiments with the VIP receptor antagonists VIP [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (16) (14) did not affect the response to capsaicin. Indeed, in our preparations, these antagonists failed even to block the secretory response to serosally applied VIP (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, VIP receptor desensitization did not affect the I sc response to capsaicin. Similarly, experiments with the VIP receptor antagonists VIP [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (16) (14) did not affect the response to capsaicin. Indeed, in our preparations, these antagonists failed even to block the secretory response to serosally applied VIP (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the physiological role of cannabinoids in the gastrointestinal tract are becoming increasingly important because of the finding that endocannabinoids are present in the gut (32). Endocannabinoids have been shown to be physiological regulators of gastrointestinal motor functions (27,33), but their role in the modulation of intestinal secretion under normal conditions has not been extensively investigated. However, there are recent data to show that an endogenous cannabinoid tone is important in regulating the extent of the secretory response to cholera toxin (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although the guinea pig ileum has long served as a useful bioassay for describing the inhibitory action of cannabinoids on intestinal transit observed in the mouse or rat in vivo, it is important that isolated ileal tissues from the latter species are used for studying cannabinoid effects. First, because a large number of models of disturbed intestinal motility of man have been created using the rat and mouse (Izzo et al, 1999;2001;Mascolo et al, 2002;Mathison et al, 2004), and second, to date, the guinea pig has not been employed for investigating cannabinoid effects on ileal transit in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In the rat ileum, the mRNAs of both cannabinoid receptors and their expression have been both identified and mapped in the myenteric plexus Valenti et al, 2005;Duncan et al, 2008). Furthermore, a number of endogenous cannabinoid ligands, exemplified by arachidonylethanolamide (AEA) and 2-arachidonylglycerol (2-AG), (Gomez et al, 2002;Mascolo et al, 2002;Izzo et al, 2003;Fegley et al, 2005;Valenti et al, 2005), along with the mechanisms for their enzymatic inactivation (Katayama et al, 1997), have been shown to be present in the rat ileum. Therefore, the purpose of this study was to investigate whether the rat ileum myenteric plexuslongitudinal muscle (MPLM) preparation served as a suitable and robust in vitro ileal cannabinoid receptor bioassay by assessing the interaction between representatives of the four main classes of cannabinoid receptor agonists, that is AEA, 5-(1,1-dimethylheptyl)-2-[5-hydroxy-2-(3-hydroxypropyl)-cy clohexyl]-phenol (CP 55,940), D 9 -tetrahydrocannabinol (D 9 -THC) and (R)-(+)-[2,3-dihydro-5-methyl-3-(4-morpholinyl methyl)pyrrolo[1,2,3-de]-1,4-benzoxazin-6-yl]-1-naphthalen ylmethanone mesylate (WIN 55,, with the CB1 and CB2 receptor selective antagonist /inverse agonists rimonabant and SR 144 528 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils release elastases and superoxide-derived free radicals that directly damage tissues. Platelets release 2-arachidonoil glycerol (2-AG), an endogenous cannabinoid, that regulates intestinal and vascular tones 2,3) .…”
Section: Introductionmentioning
confidence: 99%